Does IFRS convergence really increase accounting qualities? Emerging market evidence - Fuad Fuad; Agung Juliarto; Puji Harto (Journal of Economics, Finance and Administrative Science, 2019)
This study aims to examine whether International Financial Reporting Standards (IFRS) convergence process adds value to the accounting quality dimensions, including accruals quality, earnings smoothing, timely loss recognition and earnings persistence. Design/methodology/approach It analyzes the hypothesis of accounting quality changes in post-IFRS convergence by using the univariate and multivariate statistics. Particularly, the authors rely on panel data analyses using industrial companies' data from 2008 until 2014, comprising 3,861 firm-years observations, in Indonesia. Findings The results indicate that there is no conclusive evidence that all accounting quality dimensions including accruals quality, earnings smoothing, timely loss recognition and earnings persistence increased in post-IFRS convergence. Practical implications The findings of this study may help regulators and standard setters to consider future adoption of IFRS, mostly to figure out the best "formula" to increase the usefulness of accounting information in post-IFRS convergence. Originality/value Rather than doing piecemeal work, the current study focuses on IFRS convergence on a broader aspect of accounting quality dimensions. It also focuses on the convergence process of IFRS as an alternative of full adoption, which has been the focus of many research studies.
Keywords: 330; IFRS convergence; Accounting quality; Accruals; Earnings smoothings; Timely lossrecognition; Earnings persistence